A Hydrogen Bond Rationale for the Enantioselective beta-Alkenylboration of Enones Catalyzed by O-Monoacyltartaric Acids - Grimblat, Nicolas (2014)
DFT calculations suggest that O-monoacyl L-tartaric acids catalyze the asymmetric conjugate alkenylboration of enones through transition structures that are stabilized by hydrogen-bonding interactions. Formation of a fivemembered acyloxyborane is proposed. The hydrogen of the free carboxy group derived from the catalyst interacts with the carbonyl group of the cyclic acyloxyborane, stabilizing the transition structure and reducing the flexibility of the system. Additional stabilizing nonclassical CH···O hydrogen-bond interactions seem to determine the observed enantioselectivity.